A Novel “回” Pattern Branch Antenna for 3G\4G\WLAN\Bluetooth\Navigation Applications - Tangyao Xie; Jianguo Yu; Yao Li; Zhen Yu; Ziheng Lin (International Journal of Antennas and Propagation)
This study proposes and designs a multiband branch antenna with a structure that imitates the Chinese classical pattern structure. The antenna radiator’s structure is a symmetrical rectangular stub fused with a Chinese classical pattern structure, and the rectangular stub is bent so that the outer and inner stubs are coupled to each other to generate multiple frequency bands. Microstrip line feeding is the feeding mode, and the grounding plate is a trapezoidal structure formed by subtracting two triangles from a rectangle. The overall size of the antenna is 60 × 60 × 1.6 mm3, and the dielectric board adopts FR4. The substrate dielectric constant εr = 4.4, the thickness h = 1.6 mm, and the dielectric loss tangent tanδ = 0.02. For antenna modeling and parameter optimization, HFSS electromagnetic simulation software is used. The antenna can cover 1.49 to 1.60 GHz, 1.87 to 2.51 GHz, and 4.63 to 5.34 GHz and generate three main frequencies: 1.57, 2.15, and 5.06 GHz, according to test result. The antenna has omnidirectional radiation characteristics and can be widely used in future mobile communication network coverage.